2017
DOI: 10.1172/jci89162
|View full text |Cite
|
Sign up to set email alerts
|

Nasal neuron PET imaging quantifies neuron generation and degeneration

Abstract: Olfactory dysfunction is broadly associated with neurodevelopmental and neurodegenerative diseases and predicts increased mortality rates in healthy individuals. Conventional measurements of olfactory health assess odor processing pathways within the brain and provide a limited understanding of primary odor detection. Quantification of the olfactory sensory neurons (OSNs), which detect odors within the nasal cavity, would provide insight into the etiology of olfactory dysfunction associated with disease and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…In apparent contrast to the regenerative capacity exemplified by the manipulations described above, our group and others have shown that the OE of elderly humans often contains large areas of the epithelium devoid of neurons and GBCs (Nakashima et al, 1984;Holbrook et al, 2005. Moreover, the same has been noted in aged mice (Kondo et al, 2009;Van de Bittner et al, 2017).…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…In apparent contrast to the regenerative capacity exemplified by the manipulations described above, our group and others have shown that the OE of elderly humans often contains large areas of the epithelium devoid of neurons and GBCs (Nakashima et al, 1984;Holbrook et al, 2005. Moreover, the same has been noted in aged mice (Kondo et al, 2009;Van de Bittner et al, 2017).…”
Section: Introductionmentioning
confidence: 80%
“…In the case of the olfactory epithelium (OE), a pseudostratified neuroepithelium lining the nasal cavity, tissue stem cells are activated in response to damage and can replace cells that were lost, including the olfactory sensory neurons (OSNs). The regenerative capacity for OE stem cells after injury has been reported in several injury models (Graziadei et al, 1979;Morrison and Costanzo, 1989;Schwob et al, , 1999. Two separate populations of basal cells act as stem cells in the OE.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this issue, Van de Bittner et al describe a promising step toward solving this problem (5). Specifically, the authors discovered and characterized a new PET radiotracer, [ 11 C]GV1-57, which, they conclude, labels the mature olfactory sensory neurons (OSNs) of the olfactory epithelium, the tissue involved in recognizing smells ( Figure 1).…”
Section: In Vivo Imaging With Petmentioning
confidence: 99%